Bugden, Roberta. Cricket - Barrett, Terra
Roberta Bugden's father Hiram Young's cricket team. Description of photo: This is one team not too many people will remember. It's the 1926 Guards Athletic Association Cricket team. In those days when cricket was one of the top sports the Guards team travelled to Grand Falls and defeated the paper town for the first time to win the cup. Members of the team were; front (left to right) Ralph Stick, John Ayre. Centre - Ed Taylor, Alex Campbell. Tom Sparkes, H. Salter. Back - D. P. Duff, Ken Trenchard, Charlie Quick, R. Parsons, Eric Holden, Hiram Young.